ANALISIS KEBUTUHAN REMAJA PADA SISWA DI MTS DARUL ANWAR AL HIKAM JUNGKAT KABUPATEN MEMPAWAH - Siti Maulidiyah; Yuline Yuline; Amallia Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the needs of adolescents in MTS Al Hikam Darul Anwar Jungkat students, Mempawah Regency. The problem of this research is how the needs of teenagers in MTS Al Hikam Darul Anwar Jungkat students, Mempawah Regency. The method used is a quantitative descriptive method in the form of a survey. This study uses a population of 70 respondents. This research uses indirect communication techniques with tools such as questionnaires or questionnaires. Data analysis technique using percentage calculation. The results showed that the need for affection got a percentage of 53.85% in the good and very good categories. The results of the study that showed the need for participation and were accepted in the group got a percentage of 31.25% in the good and very good categories. The results of the research show the need for achievement to get a percentage of 48% which indicates the good and very good categories. The result of the research shows that teenagers need to get a philosophy of life with a percentage of 81.25% which indicates good and very good categories.